Investigation of the Effects of Some Operating Parameters by Using Anionic and Cationic Flocculants for Removing Solid Material in the Lignite Wastewaters - Sarioglu, M.; Cebeci, Y.; Beyazit, N. (Asian Journal of Chemistry, 2010)
In this study, the effects of various operating parameters (pH, stirring rate, flocculant concentration, stirring time, flocculant feeding rate) on flocculation of lignite coal wastes were investigated. Experimental data indicated that the cationic flocculant were affected least by pH changes while anionic flocculant was affected most. Furthermore, it has been determined that there will be considerable increase in the settling rate if the other parameters are controlled well.